Optimalisasi Pembelajaran: Dampak Penggunaan Bahan Ajar berbasis TPACK terhadap Hasil Belajar Fikih Siswa Kelas V - Jakaria, Abdul Rasyid; Damopolii, Muljono; U, Muhammad Shabir (Al Asma: Journal of Islamic Education, 2025)
This study aims to determine the learning outcomes of fifth-grade Jurisprudence students who are taught with and without using Technological Pedagogical and Content Knowledge (TPACK)-based teaching materials, as well as to examine the effect of using TPACK-based teaching materials on improving student learning outcomes. The population in this study were all fifth-grade students of MI Al-Abrar Makassar City which amounted to 79 people, consisting of 37 students in class V A and 42 students in class V B. This research method uses a quantitative approach with data collection techniques through tests. Data analysis used descriptive statistical data analysis and inferential statistical data analysis. The results of the analysis showed that students taught using TPACK-based teaching materials experienced a more significant increase in learning outcomes compared to students taught without TPACK-based teaching materials. Thus, it can be concluded that the use of TPACK-based teaching materials has a positive effect on the learning outcomes of Jurisprudence subjects of grade V students.